Alexander Graham Bell A Life Story - Joseph, Mary (Sterling Group, 2012)
Meet Alexander Graham Bell -- pioneering educator and inventor of the telephone. The story of Aleck's world-changing invention and his struggle to perfect it is told in level-appropriate language and detailed illustrations. A Level 3 first reader.
Keywords: Autobiography & Biographies( Nigeria); Memoirs; Non Fiction